Promotion of Peanut (Arachis hypogaea L.) Growth by Plant Growth-Promoting Microorganisms - Edvan Teciano Frezarin; Carlos Henrique Barbosa Santos; Luziane Ramos Sales; Roberta Mendes dos Santos; Lucas Amoroso Lopes de Carvalho; Everlon Cid Rigobelo (Microbiology Research, 2023)
Brazil is an important peanut producer, but despite its high production, there still needs to be an inoculant for the peanut crop. In addition, the use of microorganisms that promote plant growth (PGPM) is not common, and this crop is highly dependent on chemical fertilizers. An excellent alternative to reduce the use of fertilizers and chemical inputs in peanut crops while reducing the production cost and environmental impact is the use of PGPM. The objective of this study was to evaluate the effects of Azospirillum brasilense, Bacillus subtilis, Bradyrhizobium japonicum, and Trichoderma harzianum as single inoculants and co-inoculants on the growth promotion and productivity of peanuts in greenhouse and field conditions. In the greenhouse, the experiment was conducted with 12 treatments with six repetitions. In the field conditions, the experiment was conducted with five treatments with four repetitions. Both experiments were conducted in randomized blocks. In general, all the microorganisms evaluated in the present study promoted increases in root dry mass, shoot dry mass, phosphorus concentrations, and plant height in the greenhouse and under field conditions compared with the control. Interestingly, the mixtures of microorganisms inoculated in peanut plants did not promote greater plant growth and development compared with inoculations of the microorganisms separately. Specifically, in the field, the highest productivity was found for the inoculation of B. japonicum alone. The PGPM evaluated in the present study for peanut crops generally promoted some increases in productivity in greenhouse and field conditions.